Influence of Nb-doping on the local structure and thermoelectric properties of transparent TiO2:Nb thin films - Ribeiro, , J. M.; Correia, Filipe C.; Kuzmin, Alexei; Jonane, Inga; Kong, M.; Goñi, Alejandro R.; Reparaz, Sebastian; Kalinko, Aleksandr; Welter, Edmund; Tavares, C. J.M. (Elsevier Ltd, 2020)
Transparent n-type niobium-doped titanium dioxide thin films (TiO2:1.5 at.%Nb) with pronounced thermoelectric properties were produced from a composite Ti:Nb target by reactive magnetron sputtering. The thin films were comprehensively characterized by X-ray diffraction, X-ray photoelectron spectroscopy, optical spectroscopy, electrical conductivity, and thermoelectric measurement techniques. The local structure of the thin films was investigated in detail by X-ray absorption spectroscopy at the Ti and Nb K-edges. A set of radial distribution functions were extracted from the simultaneous analysis of EXAFS data at two absorption edges using the reverse Monte Carlo method. It was found that Nb dopant atoms modify the local environment of the films, but their average structure remains close to that of the anatase phase. This conclusion is also supported by the ab initio simulations of XANES. A very high absolute Seebeck coefficient (S = 155 μV/K) for n-type TiO2 was achieved with Nb doping, yielding a maximum power factor and thermoelectric figure of merit of 0.5 mW m−1 K−2 and 0.18 at a temperature of 300 K, respectively, for a 150 nm thick film. From frequency-domain thermoreflectance experiments, a thermal conductivity value of 1.3 W m−1 K−1 was obtained for the optimized TiO2:Nb film.
The experiment at HASYLAB/DESY was performed within the project I-20180036 EC. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020. Filipe Correia is grateful to the Fundação para a Ciência e Tecnologia (FCT, Portugal) for the Ph.D. Grant SFRH/BD/111720/2015 . Joana Ribeiro is grateful to the Project WinPSC - POCI-01-0247-FEDER-017796, for the research grant, co-funded by the European Regional Development Fund (ERDF) , through the Operational Programme for Competitiveness and Internationalisation (COMPETE 2020), under the PORTUGAL 2020 Partnership Agreement. The authors acknowledge the funding from the following institution Fundação para a Ciência e Tecnologia (FCT, Portugal) /PIDDAC through the Strategic Funds project reference UID/FIS/04650/2013. The Spanish Ministry of Economy, Industry, and Competitiveness through the “Severo Ochoa” Program for Centers of Excellence in R&D (SEV-2015-0496), projects No. MAT2017-90024-P (TANGENTS)-EI/FEDER and MAT2015-70850-P (HIBRI2), and the Generalitat de Catalunya through grant 2017-SGR-00488 . M. K. acknowledges the Ph.D. programme in Materials Science from Universitat Autonoma de Barcelona in which she is enrolled.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; EXAFS; Seebeck; Sputtering; Thermoelectric; Thin films; TiO2:Nb; XANES